THE INFLUENCE OF SERVICE QUALITY AND LOCATION ON PATIENT LOYALTY AT TRISAKTI DENTAL HOSPITAL MEDIATED BY PATIENT SATISFACTION - Khalda Fathiah Tuffahati; Hendra Achmadi (SEAN Institute, 2023)
Established in 2002, RSGM-P FKG Universitas Trisakti is a specialist dental and oral hospital located in West Jakarta. Hospital used to be seen as social endeavour and now shifted into socio-economics ventures. In the competitive field of health services, hospitals strive to create strategies to maintain and even increase profits. An important key to obtaining these profits is by paying attention to patient loyalty. Patient loyalty can be achieved if patient satisfaction and trust are met. This can be happened if the company can provide a good quality service and also strategic location to This research was conducted to analyze the influence of service quality and location on patient loyalty at RSGM-P FKG Universitas Trisakti with the mediation of patient satisfaction. Sampling was carried out using the purposive sampling method. The inclusion criteria in this study were independent patients or general patients who received treatment at RSGM-P FKG Universitas Trisakti for the past 2 years with a minimum of 2 visits. In this study there were 160 respondents who met the inclusion criteria. Data collection was carried out using questionnaire by google form. Data analysis in this study used the PLS-SEM (Partial Least Squares - Structural Equation Modeling) method using SmartPLS software version 4.0.6.9. The results showed that service quality and location have positive and significant effects on patient satisfaction and patient loyalty and this study also proves that patient satisfaction mediated service quality and location towards patient loyalty positively and significantly.